Six Key Elements of MLOps - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn about six key elements of MLOPs based on the best-selling book Practical MLOps Topics include: * Source Code Management * Continuous Integration and Continuous Delivery * Development Environment * Deploy Environment * Microservices including Flask and FastAPI * Business Logic.